Case of lamotrigine‐induced drug adverse reaction under tocilizumab treatment with clinical and virological features of drug‐induced hypersensitivity syndrome. Issue 6 (22nd March 2018) - Iriki, Hisato; Ouchi, Takeshi; Ito, Hiromi; Sawada, Miho; Mukai, Miho; Nomura, Hisashi; Baba, Yuko; Adachi, Takeya; Funakoshi, Takeru; Amagai, Masayuki; Takahashi, Hayato
Abstract: The pathological mechanisms and immunological kinetics of drug‐induced hypersensitivity syndrome (DIHS), including the relevance of interleukin (IL)‐6, remain unclear. We report a case of drug adverse reaction that does not fulfill the diagnostic criteria of DIHS but mimics its characteristic features. Because the patient was under anti‐IL‐6 therapy at the onset, some symptoms typically seen in DIHS were absent, such as fever and leukocyte count abnormalities. However, the characteristic features of DIHS were clearly observed in the subsequent course, including the repeated recurrence of skin rash, prolonged liver dysfunction and reactivation of herpes viruses. This case suggested that IL‐6 role at the onset is not a main factor to determine the subsequent pathomechanism of DIHS and attention should be paid to the preceding therapy for achieving accurate diagnosis.